ChemInform Abstract: Modular Bifunctional Chiral Thioureas as Versatile Organocatalysts for Highly Enantioselective Aza‐Henry Reaction and Michael Addition. Issue 10 (7th March 2013) - Li, Hua; Zhang, Xu; Shi, Xin; Ji, Nan; He, Wei; Zhang, Shengyong; Zhang, Bangle
Abstract Various catalyst components are prepared from natural Cinchona alkaloids and amino acids and tested for their efficiency.